Revision of Australian species of the dung beetle genus Lepanus (Coleoptera: Scarabaeidae: Scarabaeinae): description of 10 new species from the L. australis, L. monteithi, and L. villosus species groups - Gunter, Nicole L.; Weir, Thomas A. (Zootaxa, 2019)
This publication is part in an ongoing revision of the Australian species of the genus Lepanus Balthasar, 1966 (Coleoptera: Scarabaeidae: Scarabaeinae) and revises the three species groups with simple pygidia. Keys to species within the L. australis Matthews, 1974, L. monteithi Matthews, 1974, and L. villosus Matthews, 1974 species groups are provided and a total of 10 new species are described. Within the L. australis species group, L. australis Matthews, 1974 and L. latheticus Matthews, 1974 are redescribed and four new species are described: Lepanus burnetti new species and Lepanus oxleyi new species from southeastern Queensland; Lepanus eungella new species from coastal, central Queensland; and Lepanus dukungarri new species from Australian Wet Tropics, northern Queensland. Within the L. monteithi species group, L. monteithi Matthews, 1974 is redescribed and four new species are described: Lepanus geoffi new species from Cape York Peninsula, far north Queensland; Lepanus yorkensis new species from Torres Strait and Cape York Peninsula, far north Queensland; Lepanus reidi new species from the Australian Wet Tropics and Lepanus topend new species from the northern Northern Territory. Within the L. villosus species group, L. villosus Matthews, 1974 and L. vestitus Matthews, 1974 are redescribed and two new species are described: Lepanus pseudovillosus new species and Lepanus reticulatus new species from the Australian Wet Tropics, northern Queensland. Including these descriptions a total of 43 Lepanus species are now described from Australia.